Soft Tissue Trauma to the Nose: Management and Special Considerations - Basa, Krystyne; Ezzat, Waleed H. (Facial Plastic Surgery, 2021)
The nose is one of the most common sites of facial injury due to its prominence and anatomical placement. Given its intricate anatomy, function, and high visibility, it also proves to be one of the most complex regions for repair. We provide a review of the management of soft tissue injuries to the nose, including the various reconstructive tools available and adjunctive wound care measures. We also discuss special considerations based on mechanism of injury and treatment of this condition in the pediatric population. The main goals of reconstruction should be to preserve function while achieving optimal cosmetic results in this highly visible region of the face.
Keywords: nasal trauma; soft tissue; nasal reconstruction; facial injuries